Anemia a Contributory Factor Affecting Quality of Life in Type 2 Diabete1s Mellitus Patients - Kashif, Nadia; Iqbal, Shama; Aneela Ambreen; Ahsan, Afshan (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: The study aimed to determine the prevalence of anemia in type 2 diabetes mellitus patients and its effects on the quality of life in diabetic patients. METHODOLOGY: A cross-sectional study was conducted at the Department of Pathology, Government Naseer Ullah Khan Babar Memorial Hospital, Peshawar, Pakistan. All diabetic patients admitted to the medical ward were included in this study, and their blood samples were obtained in heparinised and EthyleneDiamineTetracetic Acid (EDTA) tubes by aseptic technique after informed consent. All samples were assessed for sugar levels and complete blood count. RESULTS: 118 diabetic patients were enrolled in this study, 66% of patients were females, and 34% were males. Female patients in age groups 1, 2 and 3 were more than males, and in age group 4, all patients were male. Anemia was found in about 79% of females and 21% of male patients. CONCLUSION: Albuminuria and renal insufficiency are important factors in understanding and investigations of anemia. Diabetic patients must be screened for anemia and treated accordingly to improve the quality of life in such patients and reduce morbidity and mortality rate.